2012
DOI: 10.1177/1329878x1214300104
|View full text |Cite
|
Sign up to set email alerts
|

News Media Consumption among Young Australians: Patterns of Use and Attitudes towards Media Reporting

Abstract: Research suggests youth make active choices about how they use and respond to media. Yet publicly available information outlining patterns of youth media consumption and how content is perceived – especially in relation to reporting of issues of pertinence to youth – is limited. Using an online survey of 2296 Australians aged 16–24, we measured news media consumption and perceptions of reporting on illicit drugs. The study concluded that Australian youth are not ‘deserting’ news media; indeed, they have regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Findings reveal that the older young adult age group consumes more news from almost all media regularly compared to the younger group. Studies show that with age people consume more news and show more interest in news [2], [4], [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings reveal that the older young adult age group consumes more news from almost all media regularly compared to the younger group. Studies show that with age people consume more news and show more interest in news [2], [4], [10].…”
Section: Discussionmentioning
confidence: 99%
“…These results are contrary to the findings of Saodah Wok, Ezhar Tamam, Jusang Bolong and Abdul Mua'ti @ Zamri Ahmad (2011) [4] which found that TV news consumption is highest among youth in Malaysia. Similarly, the majority of young adults in Hong Kong watch TV for news and current affairs (Chan & Fang, 2007) [11] and as indicated in the 2007 Roy Morgan poll showing that TV is the main source of news and information for Australian youth (Lancaster, Hughes & Spicer, 2012) [10]. However, a study from the World Association of Newspapers [4] reveals that youth today view the internet as their first choice for news and information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers [21] found that newspaper readers prefer the digital channel when searching for news updates. The researcher and company [23] found that reading online newspapers such as features, international, national, regional, or local news preferred by Indian librarians.…”
Section: Resultsmentioning
confidence: 99%